Penerapan Morning Qur’an untuk Meningkatkan Hafalan Surat Pendek Siswa di MI Raudlatul Ulum Wegil Sukolilo Pati - Rufa Hindun Farhisiyati (AL-BURHAN, 2022)
This study aims to improve students abilities in facilitating memorization of the letters in the Al-Quran through the implementation of the morning Qur’an program at MI Raudlatul Ulum Wegil Sukolilo Pati village. The main problem is that the students of MI Raudlatul Ulum have difficulty in memorizing short letters, for that we need a program to improve students memorization. This type of research is field research. While this research approach is descriptive qualitative which in its implementation analyzes the data and describe it. This research is expected to improve students memorization of short letters at MI Raudlatul Ulum. The result of this study were able to find out the implementation of the morning Qur’an program at MI Raudlatul Ulum and find out the inhibiting and supporting factors for the implementation of the morning Qur’an program at MI Raudlatul Ulum.